Nanoparticle-ultrasound synergy: an emerging theranostic paradigm for breast and gynecologic cancers - Yang, Tian; Lou, Yelin; Ying, Zhuopeng (Frontiers in Oncology, 2025)
Breast cancer (BC), cervical cancer (CC), and ovarian cancer (OC) are among the most prevalent and life-threatening malignancies affecting women worldwide. While conventional therapies have improved patient outcomes, they often result in suboptimal survival and quality of life. In recent years, ultrasound (US) has emerged as a promising therapeutic tool, not only for its well-established role in diagnostic imaging but also for its safety, deep tissue penetration, and real-time capabilities. The integration of US with nanotechnology has further expanded its potential, enabling nanoparticles (NPs) to function as contrast agents, drug delivery vehicles, and energy mediators in cancer theranostics. This review explores the synergistic effects of NPs and US in the diagnosis and treatment of breast and gynecologic cancers, with a focus on OC and CC, while also including BC due to its clinical significance and shared imaging modalities. We examine the biophysical mechanisms underlying US-based therapies, the design of multifunctional nanoplatforms, and their applications in enhanced imaging, high-intensity focused ultrasound (HIFU), sonodynamic therapy (SDT), and US-triggered drug delivery. Finally, we discuss the translational challenges and future prospects of these innovative technologies, emphasizing their potential to transform the clinical management of BC, CC, and OC.